HIF-1α RNAi Combined with Asparagus Polysaccharide Exerts an Antiangiogenesis Effect on Hepatocellular Carcinoma In Vitro and In Vivo. (23rd July 2021) - Zhu, Tingting; Cheng, Ziwei; Peng, Xiaolin; Xing, Dongwei; Zhang, Minguang
Abstract : Background . Hepatocellular carcinoma (HCC) is the main form of primary liver cancer and is one of the most prevalent and life-threatening malignancies globally. Hypoxia activates hypoxia-inducible factor-1 α (HIF-1 α ), which is the key factor in promoting angiogenesis in HCC. Currently, there are few studies on the effects of HIF-1 α -targeted gene therapy combined with traditional Chinese herbal extracts. Objective . We investigated the effects of HIF-1 α RNA interference (RNAi) combined with asparagus polysaccharide (ASP) on HCC in vitro and in vivo. Methods . CCK-8, wound-healing, transwell, and human umbilical vein endothelial cell tube formation assays were performed to evaluate the proliferation, migration, invasion, and angiogenesis of HCC cells in vitro. In addition, western blotting, qPCR, and immunohistochemistry were performed to detect the expression of HIF-1 α, vascular endothelial growth factor, AKT, p-AKT, ERK, p-ERK, and CD34 in HCC cells. Results . The combination of HIF-1 α RNAi and ASP significantly inhibited the proliferation, migration, invasion, and angiogenesis of SK-Hep1 and Hep-3B cells compared with the use of HIF-1 α RNAi or ASP alone. In addition, this combined treatment was shown to exert these effects by regulating the PI3K and MAPK signaling pathways. These results were observed both in vitro and in vivo. Conclusion . Our study indicates that HIF-1 α RNAi combined with ASP inhibits angiogenesis in HCC via the PI3K and MAPK signaling pathways. Thus, we suggest that this combination may be an effective method for the comprehensive treatment of HCC, which may provide new ideas for the treatment of other malignant tumors.